Gut Microbiome Characteristics in IgA Nephropathy: Qualitative and Quantitative Analysis from Observational Studies - Han, Shisheng; Shang, Li; Lu, Yan; Wang, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
Background Recent data indicate the importance of gut-kidney axis in the pathogenesis of Immunoglobulin A nephropathy (IgAN). Growing evidence suggests the alterations of diversity and composition of gut microbiome among patients with IgAN, however, the details are not yet fully understood. Methods Eligible studies comparing the gut microbiome between patients with IgAN and non-IgAN individuals were systematically searched from PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, and ClinicalTrials.gov. The primary outcomes were alpha- and beta-diversity, and the differences in gut microbiota composition between patients with IgAN and non-IgAN persons. Qualitative analysis and meta-analysis were performed according to available data. Results Eleven cross-sectional studies, including 409 patients with IgAN and 243 healthy controls, were enrolled. No significant differences in the diversity and enrichment of gut bacteria were found between IgAN and healthy individuals, whereas the beta-diversity consistently showed significant microbial dissimilarities among the two groups. Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria, Fusobacteria, and Verrucomicrobia were the dominant phyla, however, no significant differences were found between IgAN patients and healthy controls at the phylum level. The genera, Streptococcus and Paraprevotella showed a higher proportion in patients with IgAN compared to healthy individuals, whereas Fusicatenibacter showed a lower abundance according to meta-analysis. Qualitative analyses suggested that Escherichia-Shigella might be increased in IgAN patients; the genera, Clostridium, Prevotella 9,and Roseburia, members of Ruminococcaceae and Lachnospiraceae families, were likely to have decreased abundances in patients with IgAN compared to healthy individuals. Conclusion Gut microbiota dysbiosis was demonstrated in IgAN, which might be involved in the pathogenesis of IgAN. Further studies are needed to confirm the findings of this study, due to the substantial heterogeneity. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier PROSPERO (CRD42022304034).